Índice de fragilidade financeira aplicado ao setor público e a transparência fiscal: análise de dez municípios mineiros - Silva, Raquel Regina (2024)
Research carried out at national and international levels relates the level of fiscal transparency with socioeconomic, political and fiscal variables. This study aimed to verify whether the Level of Fiscal Transparency (dependent variable) is explained by the Financial Fragility Index Applied to the Public Sector (IFFSP), Personnel Spending and Investments (independent variables). The IFFSP was created based on Minsky's theory (1986), by Ferrari Filho, Terra and Conceição (2010), whose application summarizes the performance of public finance revenue and expenditure flows. The result obtained makes it possible to classify them into one of the three positions described by Minsky (Hedge, Speculative or Ponzi). The 10 municipalities with the highest GDPs in the intermediate geographic regions of Pouso Alegre and Varginha, in the state of Minas Gerais, were analyzed. For this research, the period from 2021 to 2023 was considered for data collection. The Fiscal Transparency Level of each of these municipalities (Extrema, Pouso Alegre, Poços de Caldas, Varginha, Alfenas, Itajubá, Passos, Três Corações, Lavras and Guaxupé) was calculated, based on information from their respective transparency portals, with based on 58 INESC indicators (2011). The independent variables were collected from the SICONFI portal of the National Treasury Secretariat. Descriptive analyses of data related to fiscal transparency were performed, segregating by budgetary dimension, and then a linear regression was performed with panel data, with random effects. The results suggest that there is no evidence of a positive relationship between the IFFSP and the Level of Transparency. There was also no significant relationship regarding the independent variable Personnel Expenses. However, the Investments variable showed a positive relationship with the Level of Fiscal Transparency of these municipalities. Therefore, it is concluded that, among the independent variables of this study, only Investments presents a significant relationship with the Level of Transparency of the 10 municipalities with the largest GDPs in the intermediate geographic regions of Pouso Alegre and Varginha in the State of Minas Gerais.